Jesus’s Confession of Ignorance and Consubstantiality - Nemes, Steven (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2024)
This essay argues that Jesus’s confession of ignorance about the day and hour of his return (Matt. 24:36; Mark 13:32) is logically inconsistent with the Nicene-Constantinopolitan doctrine of his “consubstantiality” (homoousia) with God the Father. The essay first defines “consubstantiality”, then presents three formulations of the argument, and finally rebuts a number of possible responses: from the textual originality of the phrase “nor the Son”; from the reinterpretation of “knows” as “makes known”; from the ideas of partitive exegesis and communicatio idiomatum; and from the question of the Holy Spirit’s knowledge of the things of God.